2022
DOI: 10.1101/2022.03.11.22272264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Daily Rapid Antigen Testing in a University Setting to Inform COVID-19 Isolation Duration Policy

Abstract: Importance: The suitability of the currently recommended 5-day COVID-19 isolation period remains unclear in an Omicron-dominant landscape. Early data suggest high positivity via rapid antigen test beyond day 5, but evidence gaps remain regarding optimal isolation duration and the best use of limited RATs to exit isolation. Objective: To determine the percentage of SARS-CoV-2 infected persons who remain positive via RAT on isolation day 5+ and assess possible factors associated with isolation duration. Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…We found that individuals infected with SARS-CoV-2 often had Ct values <30 beyond the five-day isolation period following SARS-CoV-2 infection currently recommended by the CDC ( Centers for Disease Control and Prevention, 2022 ). This finding is in line with other studies measuring Ct values from upper respiratory tract samples, the duration of antigen test positivity, and the duration of infectious viral load or culturable virus ( Boucau et al, 2022a ; Earnest et al, 2022 ; Ke et al, 2022 ; Landon et al, 2022 ; Lefferts et al, 2022 ). While we do not have data on infectiousness by day to clarify the exact link between Ct and infectiousness, nearly half of the individuals in this cohort had potentially infectious viral loads (Ct <30) five days after their initial detection, even in those detected later in their infection course ( Singanayagam et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…We found that individuals infected with SARS-CoV-2 often had Ct values <30 beyond the five-day isolation period following SARS-CoV-2 infection currently recommended by the CDC ( Centers for Disease Control and Prevention, 2022 ). This finding is in line with other studies measuring Ct values from upper respiratory tract samples, the duration of antigen test positivity, and the duration of infectious viral load or culturable virus ( Boucau et al, 2022a ; Earnest et al, 2022 ; Ke et al, 2022 ; Landon et al, 2022 ; Lefferts et al, 2022 ). While we do not have data on infectiousness by day to clarify the exact link between Ct and infectiousness, nearly half of the individuals in this cohort had potentially infectious viral loads (Ct <30) five days after their initial detection, even in those detected later in their infection course ( Singanayagam et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…The use of testing before exiting isolation in the 5-to 10-day period to reduce the risk of persistent infectiousness is a common strategy used by universities, including Stanford University, and other organizations. 10,16,17 Although the present study did not evaluate the association between RAT and infectivity, previous studies have shown a good correlation between RAT and viral load. [6][7][8] One recent study found that a positive RAT on day 6 was only 50% predictive of a positive culture; however, a negative RAT on day 6 was 100% predictive of a negative culture.…”
Section: Jama Network Open | Infectious Diseasesmentioning
confidence: 65%
“…These rates are similar to those previously reported for the 5-to 10-day window, ranging from 17% to 58%. 10,15,16 Individuals who tested positive on their first test were more likely to remain positive on subsequent tests with 62% of individuals testing positive on day 7 also testing positive on day 8, and 69% of those testing positive day 7 or 8 also testing positive on day 9 (Figure 1). The timing of antigen…”
Section: Discussionmentioning
confidence: 99%
“…( 21 ) This finding is in line with other studies measuring Ct values from upper respiratory tract samples, the duration of antigen test positivity, and the duration of infectious viral load. ( 4, 2224 ) While we do not have data on infectiousness by day to clarify the exact link between Ct and infectiousness, nearly half of the individuals in this cohort had potentially infectious viral loads (Ct<30) five days after their initial detection, even in those detected later in their infection course ( 25 ). By day 10, the number of individuals with Ct<30 was substantially reduced but still high.…”
Section: Discussionmentioning
confidence: 98%